Demian Wheeler and David E. Conner (eds.), Conceiving an Alternative: Philosophical Resources for an Ecological Civilization. (6th August 2021) - Schilbrack, Kevin
Abstract : Demian Wheeler and David E. Conner (eds.), Conceiving an Alternative: Philosophical Resources for an Ecological Civilization (Anoka: Process Century Press, 2019), 313 pp., $18.00 (pbk), ISBN: 978-1940447407.